Lahar paraisong abo - Chionglo, Mel.; Lee, Ricardo (Quezon City Star Cinema Production., 1996)
Filmed entirely in the devastated areas in Pampanga, It tells the story of entire barrio's dtruggle for survival and dignity after it is struck by the destructive volcanic miudflow known as Lahar.
VCD
Director, Mel Chionglo ; writer, Ricardo Lee
Dawn Zulueta, Tonton Guitierres, Jacklyn Jose
Keywords: Lahar--Philippines--Zambales.; Disasters--Philippines--Zambales.